2022
DOI: 10.1038/s41467-022-28579-z
|View full text |Cite
|
Sign up to set email alerts
|

In-situ transfer vat photopolymerization for transparent microfluidic device fabrication

Abstract: While vat photopolymerization has many advantages over soft lithography in fabricating microfluidic devices, including efficiency and shape complexity, it has difficulty achieving well-controlled micrometer-sized (smaller than 100 μm) channels in the layer building direction. The considerable light penetration depth of transparent resin leads to over-curing that inevitably cures the residual resin inside flow channels, causing clogs. In this paper, a 3D printing process — in-situ transfer vat photopolymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…1). [24][25][26] For commercial resins, strategies to diminish resin cytotoxicity have started to emerge recently, [27][28][29][30] along with solutions addressing print resolution, [31][32][33][34][35][36] imaging compatibility, 33,[37][38][39] and surface modification and bonding. 40,41 Sifting through the plethora of literature for best practices can be challenging for researchers who are new to this rapidly growing field.…”
Section: Introductionmentioning
confidence: 99%
“…1). [24][25][26] For commercial resins, strategies to diminish resin cytotoxicity have started to emerge recently, [27][28][29][30] along with solutions addressing print resolution, [31][32][33][34][35][36] imaging compatibility, 33,[37][38][39] and surface modification and bonding. 40,41 Sifting through the plethora of literature for best practices can be challenging for researchers who are new to this rapidly growing field.…”
Section: Introductionmentioning
confidence: 99%
“…Pore size plays a crucial role in promoting the attachment of cells onto the scaffold, as well as their migration into and proliferation within the construct. One of the most important benefits of 3D printing techniques is that they allow for precise control over architectural details, and therefore the determination of an optimal pore size or range is critical in the development of scaffolds of increasing scale and complexity [ 93 , 188 ]. Lim et al evaluated the effect of pore size on the in vivo efficacy of biphasic calcium scaffolds composed of HA and β-TCP in rabbit calvarial defects and found that larger pore sizes (1200–1400 µm) were associated with enhanced bone formation, although this effect disappeared at 8 weeks [ 189 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%
“…Its huge potential in the simple and fast production of materials with special properties leads to a wide range of potential applications [ 2 ]. Practical applications include, for instance, coatings [ 1 , 3 ], tissue engineering [ 4 , 5 ], photolithography [ 6 , 7 , 8 , 9 ], microfluidic device fabrication [ 10 , 11 ], 3D prototyping [ 12 , 13 , 14 , 15 ], and 4D bioprinting [ 16 , 17 ]. Significant characteristics of photopolymerization include the solvent-free formulation, ability to cure at ambient temperature conditions (which is especially important for heat-sensitive materials), and low energy consumption, as well as spatial and temporal control over the polymerization [ 1 ].…”
Section: Introductionmentioning
confidence: 99%